Assessment of Research and Statistical Related Processes in selected Institutions of Higher Learning Kenya - Chege, Nancy Waitherero (My University, 2012)
Institutions of higher learning are mandated to conduct applied research and promote innovations among other functions. The purpose of this study was to assess four research and statistical-related processes in three institutions of higher learning namely, Jomo Kenyatta University Agriculture and Technology (JKUAT), Kenya Technical Teachers College (KTTC) and Kenyatta University (KU). The research and statistical related processes were identified after a one- to -one consultation with the people in charge of crucial research departments in the three institutions. The four tasks included, assessment of an approach that could be used to develop content for an innovation policy document at RPE, assessment of some aspects of an instrument used in monitoring and evaluation of innovation projects at RPE, assessment of training in research and statistical methods at JKUAT and KTTC, and finally an assessment of data analysis procedures of one dataset from ASARECA project based at KU. A qualitative approach was used to gather information and analyse data on appropriate content of the innovation policy documents. Two key informants, purposively selected from RPE provided the necessary textual data for this assessment. The tool used to collect the data was an open interview schedule (see appendix I for the schedule). Qualitative procedures were used to analyse the data including transcription of textual data, data display, data reduction and drawing of conclusions to develop content of the policy. Two aspects of the instrument used in monitoring and evaluation of innovation projects were assessed. Data were collected from innovation proposals forwarded to RPE. More data were also collected during the actual monitoring and evaluation process. The data were entered in excel and summaries made using tables and graphics. Assessment of training was done in two folds; One, through assessment of use of Moodle, (a learning management system), in teaching of an MSc course in research methodology at JKUAT. The data for this assessment were collected using an observation profoma form the SSC Moodle web site which hosted the course. The data were later analysed using descriptive statistics including the frequency distributions and measures of central tendencies. The second fold was an assessment of teaching research methods at KTTC. Statistical Package for Social Sciences (SPSS) was used in the analysis. The dataset from KU was analysed in stages, first step was to use the Meta data availed and formulate research questions to guide the analysis process. Pivot tables were then created in excel to summarize the measurements of the variables. Exploratory analysis in GenStat and R softwares followed before doing hypothesis testing and statistical modeling. The study revealed that a qualitative approach can be used to gather information from key informants to generate content for innovation policy document. It also showed that the field of application of most of the innovation projects at RPE, JKUAT is agriculture. Among the collaborators suggested in all the proposals, none was a biometrician/research methods professional, or an economist, very few entrepreneurs were included. According to the findings, the learning forums on Moodle site were not fully utilized. As in assessment of teaching at KTTC, the rating of availability of resource materials for students was low. The findings from analysis of data from KU revealed that organizing the analysis such that it begins with an outline of analysis objectives, followed by creation of pivot tables, carrying out exploratory analysis, testing hypotheses and doing a regression analysis towards the end. The study recommends that; a policy document be formulated at RPE to guide the management of the innovation projects, Biometricians /RM professionals and economists be included as collaborators, innovators from all fields be encouraged to participate by RPE, use of Learning Management Systems be promoted by the e-learning department to enhance teaching at the University, Simplified manuals in research and statistical methods be availed at KTTC for the diploma students and correct procedures for data analysis be followed in order to produce accurate and reliable findings from research